Endoscopic gastroenterostomy: techniques and review. Issue 5 (September 2017) - Irani, Shayan; Baron, Todd H.; Itoi, Takao; Khashab, Mouen A.
Abstract : Purpose of review: Gastric outlet obstruction (GOO) can result from benign and malignant causes. Until recently, surgical gastrojejunostomy was the treatment of choice for patient with benign and malignant GOO with a good functional status. Endoscopic placement of luminal self-expandable metal stents is currently widely accepted as the first line of treatment for malignant GOO because of its effectiveness and minimally invasive nature. The main shortcoming of luminal stents is the high incidence of recurrent GOO most commonly because of tumor ingrowth/overgrowth. More recently, endoscopic ultrasound (EUS)-guided gastroenterostomy (EUS-GE) has emerged as an alternative to both luminal stent placement and surgical gastrojejunostomy. Advantages of EUS-GE include its minimally invasive nature, efficacy and low incidence of recurrent GOO in cancer patient. We will describe five different techniques to perform this novel and rapidly evolving procedure using a biflanged, lumen-apposing metal stent and compare benefits and risks of each approach. These approaches include antegrade EUS-GE or 'traditional/downstream' and 'rendezvous' methods, retrograde EUS-GE or 'enterogastrostomy, '17 (EPASS), and antegrade EUS-GE 'direct' method. Recent findings: A preprocedural computed tomography scan allows the proximity of the duodenum or jejunum to the stomach to be determined and to assess for the presence of significant ascites, which is a contraindication to EUS-GE. Technical success rates even in the early studies approximate 90%, regardless of the technique used. Clinical success rates have been exceptionally high as well, with only a minority of patients experiencing persistent symptoms despite technical success. One procedure-related death has been reported so far with an overall low morbidity. Pain, bleeding, pneumoperitoneum and peritonitis have been reported in one patient each. However, duration of follow-up in these studies has been short. Summary: We describe five different techniques to performing EUS-GE. Early studies show excellent efficacy. Stent misdeployment/displacement is the most frequent relevant adverse event. Prospective and preferably randomized trials with comparison to endoluminal enteral stents and surgical gastroenterostomy are needed.